REVIEW OF THE MONOGRAPH BY ALIEV B.G. “HISTORICAL GEOGRAPHY OF DAGESTAN OF THE FIRST HALF OF THE 19TH CENTURY”. MAKHACHKALA, 2021. ISBN 978-5-00128-890-9 - El'darov, El'dar Magomedovic (History, Archeology and Ethnography of the Caucasus, 2022)
The present review is devoted to a large scientific monograph “Historical geography of Dagestan in the first half of the 19th century” (Makhachkala: IHAE, ALEF, 2021. 574 p.), written by one of the founders of Dagestan historical geography, Professor, Doctor of historical sciences Bagomed Gadayevich Aliev. The information base for the author was a huge material in the form of archival and literary sources, as well as various historical and ethnographic information, collected by him during numerous expeditions to various regions of the republic. From the perspective of geography, it is important that, characterizing the socio-historical position of Dagestan, the author notes the changes in the natural environment that took place at different historical stages of the development of the republic. The features of the settlement and economic life of the peoples of Dagestan are described in a very interesting and informative way. The author does not turn away from the geopolitical studies of some foreign authors that touch upon the topic of the external borders of Dagestan. The largest section of the monograph is devoted to the spatial features and patterns of political life in the Land of Mountains. Moreover, characterizing the feudal estates and unions of rural communities, the author clearly identifies their boundaries. The paper also describes various forms of administration of the territories of Dagestan in the period under review, including the administrative structures within each of its administrative units, founded by the imperial authorities and the Caucasian military command. The author formulates deep scientific conclusions and judgments based on the historical and geographical material analyzed by him, which is very voluminous and diverse in subject matter. Ultimately, B.G. Aliev gives a complete and clear picture of what the territorial natural-social system of Dagestan was like in the first half of the 19th century.
Keywords: Dagestan; historical geography; ethnopolitical formations; fiefs; historical sources; review